Global Trends in the Relationship Between Chronic Air Pollution Exposure, Physical Activity and Lung Function in Youth Aged 5–18 Years With and Without Asthma: A Systematic Review - Samanta Gudziunaite; Kelly A. Mackintosh; Gwyneth A. Davies; Kathryn A. Jordan; Paul D. Lewis; Chris J. Griffiths; T. Alexander Swain; Melitta A. McNarry (Sports Medicine - Open)
Abstract Background Children are more susceptible to air pollution due, at least in part, to their less-developed respiratory systems and higher respiratory rates. Although the health benefits associated with physical activity are indisputable, there is considerable debate regarding whether increased exposure to, and deeper inhalation of, air pollution while being physically active negates such health benefits. Objectives The aim was to explore the relationship between air pollution and lung function and the influence of asthma status and physical activity in children and adolescents. Methods Six databases were searched following PRISMA guidelines with no date restrictions: PubMed, Web of Science, MEDLINE, EMBASE, SPORTDiscus, and Cochrane Central Register of Controlled Trials (CENTRAL). Studies were included if they: i) studied children and adolescents (5–18 years); ii) were peer-reviewed; iii) were available in the English language; and iv) reported data using previously validated tools. Results From 12,161 original records, 16 studies were included in this review. The most widely examined pollutants were particulate matter PM2.5–PM10, ozone (O3), nitrogen dioxide (NO2), nitrogen oxide (NOX), carbon monoxide (CO), and sulphur dioxide (SO2). Increased exposure to various air pollutants, particularly during outdoor physical activity, resulted in lung function deficits. This was especially evident in children and adolescents with asthma, dependent on the specific air pollutant. There was a consensus that forced expiratory volume in one second (FEV1) and forced vital capacity (FVC) decreased as air pollution concentrations increased. Notably, there was a reduction in FEV1 at both three- and four-days post-exposure to CO, PM10, and NO2. Conclusions There is a pressing need to reduce the impact of air pollution on lung function to improve health and realise the full benefits of physical activity. Given the potent and potentially long-term effects of air pollution, governments and local authorities must continue to reduce air pollution concentrations to improve the current and future health of populations globally. Key Points Increased exposure to air pollutants results in impairments of children’s and adolescents’ lung function, with the most pronounced effects observed three-to-four days post-exposure. This delayed impact suggests a prolonged risk of respiratory impairment following exposure, but further work is required to fully elucidate the timeline and associated dose-response relationship. The limited evidence available suggests that physical activity levels may be lower during periods with high air pollution concentrations, particularly in those living in urban areas or near roads. This is especially concerning for children with asthma, who are at a greater risk of experiencing poorer lung function due to the combined effects of reduced physical activity and increased pollutant concentrations. Physical activity during periods of high air pollution concentrations is tentatively suggested to deleteriously influence lung function in children and adolescents.